Long-term impact of battle injuries; Ten-year follow-up of Dutch servicemembers injured in Afghanistan - Benjamin L. Turner; Thijs T. C. F. van Dongen; Floris Idenburg; Loes de Kruijff; Eelco P. Huizinga; Eric Vermetten; Erik Hoencamp; Rigo Hoencamp (PLoS ONE, 2025)
Background Our five-year follow-up of injured service members deployed to Afghanistan showed that battlefield casualties (BCs) experience lower quality of life and higher distress than non-injured peers. This ten-year follow-up aims to extend the understanding of the long-term impact of battlefield injuries and to enrich the knowledge of long-term impacts of combat wounds. Methods Dutch service members deployed to Afghanistan (2006–2010) were divided into groups: injured by hostile actions (BCs) and two control groups—non-injured combat unit members (CG1) and non-injured staff (CG2). Data on injuries, demographics, and rank were gathered, and participants completed an online survey covering trauma, reintegration, distress, quality of life and physical and mental health. Group differences were assessed using Kruskall-Wallis tests and ANOVA. Results The mean age of participants in the BC group (n = 47) was lower than CG1 (n = 95) and CG2 (n = 64). BCs reported significantly higher levels of distress compared to control groups. Of 25 significantly different scores between the three subgroups in our five-year follow-up, all but the Work Positive PDRS subscore remained significantly different compared with the control group. Additionally, the EQ-6D and General Health SF-36 subscore were significant at five years but not this study. Conclusion Service members with battlefield injuries report significantly lower quality of life, predominantly in physical functioning, and higher psychological distress compared to non-injured peers. Most differences between BCs and non-injured peers identified in our 5Y follow-up remained significantly different. We provide recommendations to improve the quality of aftercare based on our observations (1) periodical evaluation every 3–5 years, (2) comprehensive assessment of care needs and (3) balancing disease burden and health to optimize societal and workplace integration.